2002
DOI: 10.1172/jci14340
|View full text |Cite
|
Sign up to set email alerts
|

Thyrostimulin, a heterodimer of two new human glycoprotein hormone subunits, activates the thyroid-stimulating hormone receptor

Abstract: Human thyrotropin (TSH), luteotropin (LH), follitropin (FSH), and chorionic gonadotropin are members of the heterodimeric glycoprotein hormone family. The common alpha subunit forms noncovalent heterodimers with different beta subunits. Two novel human glycoprotein hormonelike genes, alpha2 (A2) and beta5 (B5), recently have been identified. Using a yeast two-hybrid assay, the two subunits were found as potential heterodimerization partners. Immunological analyses confirmed the heterodimerization of A2 and B5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 49 publications
5
85
0
1
Order By: Relevance
“…The presence of these proteins in invertebrates suggests that they could be an ancestral form of the glycoprotein hormones. In mammals, these have been found to dimerize and activate the thyroid stimulating hormone receptor, leading to the heterodimer being called thyrostimulin (TS; Nakabayashi et al, 2002). Their endogenous physiological function, however, remains to be elucidated.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…The presence of these proteins in invertebrates suggests that they could be an ancestral form of the glycoprotein hormones. In mammals, these have been found to dimerize and activate the thyroid stimulating hormone receptor, leading to the heterodimer being called thyrostimulin (TS; Nakabayashi et al, 2002). Their endogenous physiological function, however, remains to be elucidated.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…They also identified a human homologue, called GPA2, of the common glycoprotein hormone ␣-subunit. Subsequently, it was shown that GPB5 and GPA2 heterodimerize and that the heterodimer activates the TSHR, and the term thyrostimulin was coined to describe the GPB5͞GPA2 heterodimer (10). Thus, the OGH Ϫ/Ϫ and OGH-TG mice have allowed us to investigate the physiological role of this active ␤-subunit in normal thyroid physiology, study its effects on various aspects of thyroid activity (TSH, T3͞T4, and thyroid histology), and identify key hormonal and metabolic perturbations that translate into important effects in regulation of body weight.…”
mentioning
confidence: 99%
“…Th erefore, it is questionable whether it can, indeed, heterodimerize in the circulation (Dos Santos et al 2009). Th yrostimulin heterodimerizes only aft er treatment with a bifunctional reagent and it is likely that it may be less stable than other glycoprotein hormones (Shupnik et al 1989;Nakabayashi et al 2002). Nevertheless, GPB5 does have the Cys 120 -Cys 127 disulphide bridge, which corresponds to the sixth disulphide bridge (Cys 93 -Cys 100 ) in CGβ, crucial for hCG heterodimerization ( Figure 2) .…”
Section: Th E Unique Structure Of Thyrostimulinmentioning
confidence: 99%